ANALISA PENGARUH HOLDING TIME DAN TEMPERATUR PADA PACK CARBURIZING MENGGUNAKAN LIMBAH KULIT SINGKONG TERHADAP SIFAT FISIK DAN MEKANIK BAJA 1020 - Fikri, Ali; Muhammad, Muhammad; Rahman, Abdul; Putra, Reza; Habibi, Muhammad (E-Journal Universitas Malikussaleh, 2023)
The purpose of this study to determine the effect holding time on increasing the surface hardness of AISI 1020 steel material and analyzing the physical and mechanical properties of the results pack carburizing cassava peel waste on AISI 1020 steel. Process pack carburizing in this study have variations temperature 875oC and 900oC withholding time 60 minutes, 80 minutes, 100 minutes and 120 minutes. The catalyst used in this study was a carbonate compound, namely 20% BaCo3 to accelerate the reaction of adding carbon. The research results show that pack carburizing from cassava peel waste carbon can increase the surface hardness of AISI 1020 steel or part of the mechanical properties of the material. Testing at a temperature of 875oC withholding time 60 minutes which is 10.7 HRC and is the lowest value in the study while the highest hardness value occurs at a temperature of 900OC withholding time 120 minutes is 48.2 HRC. Microstructure observation results (metallography) on the edges indicates the martensite phase. The more martensite phase, the higher the value of the surface hardness of the steel material in the same direction as the effect of the length of holding time(holding time)